Automatic Network Failure Detection Feature in IT Helpdesk Application PKG V2 at PT. Petrokimia Gresik - Fauzan, Subhan; Sukaridhoto, Sritrusta; Khoironi, Khoironi (Universitas Nahdlatul Ulama Surabaya, 2024)
The IT Helpdesk application at PT Petrokimia Gresik faced significant challenges with the initial version (V1), which relied heavily on manual incident reporting. This led to delays and errors, especially in managing urgent issues for high-priority users, such as executives. To address these limitations, Helpdesk TI PKG V2 was developed, incorporating an automatic network failure detection feature. This enhanced version integrates Zabbix, an open-source network monitoring tool, to detect network issues like high latency, packet loss, and downtime in real-time, without requiring user input. When an anomaly is detected, Zabbix sends an alert to the Laravel-based backend system via webhook, where the issue is logged, and a helpdesk ticket is automatically created. Additionally, to ensure quick responses from the network support team, real-time notifications are sent to a Telegram group. This feature allows staff to receive alerts on their mobile devices, enabling faster action even when they are away from their desks. The integration of Telegram notifications ensures that network issues are promptly addressed, improving service continuity for critical users. The implementation of these features has significantly improved incident response times, reduced manual workload, and enhanced overall operational efficiency.